The Interplay Between Business Models and Entrepreneurial Capabilities in Aging Populations: Insights from Emerging Economies - Fabricio Miguel Moreno-Menéndez; Victoriano Eusebio Zacarías-Rodríguez; Pedro Emil Torres-Quillatupa; Sara Ricardina Zacarías-Vallejos; Saúl Nilo Astuñaupa-Flores; Yamill Alam Barrrionuevo-Inca-Roca; Javier Amador Navarro-Veliz; Vicente González-Prida (World)
This research examines the link between business models and entrepreneurial capabilities among social assistance program participants who are aging adults in an emerging economic environment. The research targets the insufficient use of entrepreneurial abilities in seniors to advance their active aging potential while enhancing their life quality. This study collected data from selected participants by using Osterwalder and Pigneur’s business model framework as a basis for their structured questionnaire, which followed a quantitative–qualitative method. Researchers applied Spearman’s Rho statistical methods to measure relations between business elements and skills in self-confidence, creativity, initiative, perseverance, and teamwork demonstrated by entrepreneurs. The study results clearly showed that properly executed business models create substantial growth in entrepreneurial abilities among people of advanced age. This study contributes novel empirical evidence from a rural Peruvian context, confirming that structured business model training is positively associated with entrepreneurial outcomes among elderly populations. The findings (r = 0.755, p < 0.001) support the urgency of integrating capability-building into social assistance schemes. These results emphasize how targeted training programs should empower this population since this initiative supports Sustainable Development Goals like “Decent Work and Economic Growth” (SDG 8) and “Reduced Inequalities” (SDG 10). The analysis demonstrates that teaching entrepreneurial abilities to mature individuals leads to better social entrepreneurship sustainability together with superior economic involvement and social connections.